Major complications of tibial tuberosity advancement in 1613 dogs. Issue 4 (31st March 2017) - Costa, Mario; Craig, Diane; Cambridge, Tony; Sebestyen, Peter; Su, Yuhua; Fahie, Maria A.
Abstract: Objectives: To report major postoperative complications in 1613 dogs with tibial tuberosity advancement (TTA). Study design: Retrospective case series. Sample population: Dogs (n = 1613) with cranial cruciate ligament deficiency treated with TTA. Methods: Medical records of TTAs performed between December 2007‐2013 were reviewed for age, sex, weight, contralateral stifle surgery, surgical approach, duration of preoperative lameness, presence of meniscal damage, concurrent patellar luxation and simultaneous bilateral TTA. Major postoperative complications were defined as surgical site infection (SSI) (superficial, deep, or organ/space), implant failure, fracture, patellar luxation, and meniscal tear. Results: Major complications were recorded in 13.4% of cases. Superficial SSI (incisional irritation) was diagnosed in 6.9% cases, requiring only antimicrobial therapy. Other complications included postliminary medial meniscal tear (2% incidence), deep SSI (incisional dehiscence, 1.1%), implant failure (1%), patellar luxation (1.2%), fracture (0.9%), and organ/space SSI (septic arthritis, 0.4%). Dogs with normal menisci were less likely to develop postliminary meniscal tears if the medial meniscus was released at the time of TTA ( P  < .0001). No association was detected between recorded parameters and complications, although dogs >8 years old approached significance ( P  = .05) in terms of predisposition to major complications. Conclusions: Major complications after TTA are uncommon, even in dogs with concurrent patellar luxation or bilateral simultaneous procedures. In spite of its morbidity, medial meniscal release may prevent postliminary meniscal tears.